The Implementation of Curriculum Development in Indonesian Context - Mazulfah Mazulfah; Abdurrachman Faridi; Dwi Anggani Linggar Bharati; Januarius Mujiyanto (Universitas Negeri Semarang, 2021)
This article explains the development curriculum implementation in an Indonesian context. The curriculum formulation is one of the most significant of implementation of education componen. A curriculum is defined as a set of plans and systems that describe the goals/objectives, contents, materials, and instructional techniques—a direction in order to prepare for change. In national education, the teaching and learning process plays an essential part in achieving specific educational goals. The curriculum is a dynamic component of education that is constantly changing over time. It is critical to change to keep up with societal advancements, student demands, and scientific and technological advancements. The evolution of an education curriculum in a particular country, such as Indonesia, might represent the country's progress. Indonesia's national curriculum has undergone numerous revisions. However, Pancasila and the 1945 Constitution serve as the foundation for the whole national curriculum.